Kinetic Spectrophotometric Determination of Propellant Grade Hydrazines using Thiophenes with Active Carbonyl Groups - Subramanian, Selvakumar; Narayanasastri, Somanathan; Kami Reddy, Audisesha Reddy (Defence Science Journal, 2014)
A simple, cost effective, highly sensitive and rapid kinetic spectrophotometric method was developed for hydrazines by using Thiophene-3-carboxaldehyde (3-Thienaldehyde) and 3-Butenone (E)-1,1,1-trifluoro-4-(3-thienyl) (CF3 enone). CF3 enone was prepared by crossed aldol condensation of 3-Thienaldehyde and characterized by UV-Vis, FT-IR and NMR spectra. Reactions of 3-Thienaldehyde (with catalyst) and CF3 enone (in acetonitrile medium without catalyst) with hydrazines were followed spectrophotometrically and compared. Variables such as temperature and concentration were optimized to determine hydrazines in the concentration range of 0.1 mM to 0.1 M for 3-Thienaldehyde and 0.1 mM to 1 mM for CF3 enone. Minimum detectable limits were found to be 0.2 mM (Hydrazine) and 0.1 mM (MMH ) for 3-Thienaldehyde. For CF3 enone, Minimum detectable limits were found to be 0.007 mM (Hydrazine) and 0.01 mM (MMH). Rate of the CF3 enone reaction was studied as there is gradual decrease in absorbance for the peak at 320 nm for the interaction of hydrazines. Initial rate and fixed time methods were adopted for kinetic study. CF3 enone based kinetic spectrophotometric method is rapid and sensitive with no catalyst requirement for interaction of hydrazines when compared with the classical CHO functional group based method. Defence Science Journal, Vol. 64, No. 1, January 2014, DOI:10.14429/dsj.64.3092